2013
DOI: 10.1021/jz402208z
|View full text |Cite
|
Sign up to set email alerts
|

UV-Induced Strand Breaks in Double-Stranded DNA Labeled with 5-Bromouracil: Frank or Secondary?

Abstract: Some literature reports suggest that in DNA labeled with 5-bromouracil (5BrU), near-UV photons lead to strand breaks that are formed due to the formation of a reactive uracil-5-yl radical capable of abstracting a hydrogen atom from its own or adjacent sugar moiety, which results in a direct strand break. However, other reports propose the formation of 2′-deoxyribonolactone rather than a strand break during the photodamage of 5BrU-substituted DNA. In order to resolve these contradictions, we carried out a serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…BrdU‐labeled DNA is sensitive to both ionizing and UV radiation 17–20. 2328 Although the mechanisms of SSB formation triggered by SEs and UV photons are quite different,17, 24, 25, 27, 28 both damaging agents lead to SBs in 5‐BrdU‐labeled DNA. As using a UV source is far easier than using ionizing radiation, we decided to employ the former in order to validate our methodology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BrdU‐labeled DNA is sensitive to both ionizing and UV radiation 17–20. 2328 Although the mechanisms of SSB formation triggered by SEs and UV photons are quite different,17, 24, 25, 27, 28 both damaging agents lead to SBs in 5‐BrdU‐labeled DNA. As using a UV source is far easier than using ionizing radiation, we decided to employ the former in order to validate our methodology.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, SSB occurs as a result of long‐range photoinduced electron transfer (ET) between electronically excited 5‐bromouracil and guanine 23. 24, 27 This process is strongly sequence‐dependent;23, 24 moreover, even though approximately 25 % of nucleotides are 5‐BrdUs in 1600 bp plasmids, the sequences (“hot spots”) leading to efficient photoinduced ET are quite scarce, as indicated by previous studies on DNA PCR labeled with 5‐BrdU 24. 26 As two nearby SSBs located in opposite strands are considered to be DSBs, the rare occurrence of “hot spots” in a random DNA sequence explains the lack of DSBs observed during our photochemical experiment.…”
Section: Methodsmentioning
confidence: 99%
“…8 A key process, that ultimately results in DNA strand-cleavage, involves uracil-5-yl radicals abstracting H atoms from nearby functional groups. 9,10 Alternatively, several studies have investigated the possibility that, under aerobic conditions, reaction of the uracil-5-yl radicals with molecular oxygen will form peroxyl radical intermediates (Scheme 1 (i)), and that these peroxyl radicals might be key intermediates in rationalising the activity of these halouracils. 11,12 Following this line of enquiry, Schyman et al reported in a computational study that the peroxyl radical would actually be a less efficient at H atom abstraction from deoxyribose than the uracil-5-yl parent.…”
Section: Introductionmentioning
confidence: 99%
“…4,5,1318 The uracil-5-yl • is highly reactive and is suggested to abstract a hydrogen atom from C 1' or C 2' site of the adjacent deoxyribose which ends up with DNA strand breaks. 4,5,15,18 . Li et al note that 5-BrdU in double stranded DNA is less electron affinic than in single stranded DNA which would make 5-BrdU selective for replicating DNA.…”
Section: Introductionmentioning
confidence: 99%